Analisis Yuridis Kedudukan CCTV sebagai Alat Bukti Elektronik dalam Perspektif UU ITE dan Hukum Islam - Sainal; Muh. Amin; Herman Pelani (AHKAM, 2026)
Although the use of closed-circuit television (CCTV) as electronic evidence has been widely examined under Indonesian positive law, research integrating the provisions of Law Number 11 of 2008 concerning Electronic Information and Transactions (the ITE Law) with the concept of qarinah in Islamic law remains limited. This study aims to analyze the legal status of CCTV as electronic evidence under the ITE Law and examine the legitimacy of its use from the perspective of Islamic law. This study employed a legal research method using statutory, conceptual, and shar‘i approaches. Data consisting of primary and secondary legal materials were analyzed qualitatively. The results demonstrate that CCTV constitutes valid electronic evidence under Article 5 of the ITE Law and serves as an extension of the forms of evidence recognized in Indonesian criminal procedural law. Under Islamic law, CCTV may be classified as qarinah, or an indication, that possesses evidentiary value provided that it satisfies the principles of authenticity, integrity, and information validity. The use of CCTV is also consistent with maqāṣid al-syarī‘ah, particularly the protection of life (ḥifẓ al-nafs), the protection of property (ḥifẓ al-māl), and the realization of justice (al-‘adl). These findings affirm that the concept of qarinah is adaptable to technological developments and can support the harmonization of Indonesian positive law and Islamic law within modern evidentiary systems. Accordingly, the legitimacy of CCTV has mutually reinforcing juridical and normative foundations for supporting legal certainty, justice, and public benefit. This study contributes to the development of electronic evidence law and may serve as a reference for law enforcement practices in Indonesia.